Effect of drying on the kinetics, stability of active ingredients and non- destructive testing of Backhousia citriodora (lemon myrtle) dehydrated leaves - Abdul Kahar, Ainaa (2021)
The dehydration process of lemon myrtle leaves (LML) in Malaysia is still conducted by using conventional method of drying that takes long duration thus decreasing the quality of the dried LML. To prolong the shelf life, LML has to be dried to reduce its moisture content. The present research highlighted the drying kinetics, application of heat pump drying on LML and the application of non- destructive testing on moisture content analysis of dried LML. In the present study, LML were dried by OD (40 to 60°C), VD (40 to 60°C at 50 mbar) and HPD (45°C). Both engineering properties (drying kinetics, effective moisture diffusivity and activation energy) and quality properties (colour, biochemical content and volatile content) of all dried LML were assessed and evaluated.